To Study The Clinical Profile In Patients of Ventral Hernia In A Rural Tertiary Health Care Center. - P, Ravi Chandu.; Chandak, Suresh R. (International Journal of Psychosocial Rehabilitation, 2020)
The anterior abdominal wall is the site of variety of hernias means erect posture which renders the anterior abdominal wall weak. All most all these hernias protrude through the abdominal wall to form palpable swellings. To study the etiopathogenesis of ventral hernias, To Analyse the pattern of ventral hernias, To study morbidity due to ventral hernia, To study the outcome of different surgical repair procedures. This Prospective study will be conducted in tertiary health care centre with two and half years of study duration of total sample size 60. Interpretations during study for various types of ventral hernias including role of patients sex and age, analyze pattern of hernias, different types of hernias, time gap between surgery and development of incisional hernia at post surgical site, etiopathogenesis for development of ventral hernia, site and size of different hernias, various treatments available for ventral hernias and follow up duration and complications after surgery. Ventral hernia is a common surgical complaint. Treatment options include primary anatomical repair and meshplasty.Meshplasty is standard of care now a days.